Traditional knowledge and economic significance of Berberis lycium Royle in the Lower Dir District, Pakistan - Ahmad, Latif; Ullah, Farid; Semotiuk, Andrew J.; Rashid, Wajid; Khan, Imran; Jan, Hammad Ahmad; Bussmann, Rainer W.; Ahmad, Imran (Ethnobotany Research and Applications, 2020)
Background: Berberis lycium Royle is a well-known medicinal plant, belonging to the family Berberidaceae, and is widely distributed in Lower Dir, Pakistan. Parts of B. lycium like rhizomes and berries are used by the local people as medicine and food.This research work focused on two major aspects regarding B. lycium. Firstly, to determine the various traditional and medicinal uses of B. lycium. Secondly, to document its monetary value at local markets in the study area. Methods: Semi-structured and open-ended ethnobotanical interviews, local market inquiries, field observation, and group discussions were conducted from May 2018 to October 2019 to understand ethno-botanical knowledge of B. lycium. Results: In the current study, a total of 61 local people from Dir Lower were interviewed. According to the result of our study, 37% of informants used the B. lycium for the treatment of diabetes mellitus, followed by infection (12.5%) and bone repair (10%). In terms of economic value, the fruits and rhizomes of B. lycium are also important. Locally the rhizome was sold for prices ranging between 3 and 6 USD per kilogram. Conclusion: This study concludes that local people of Dir Lower have significant medicinal as well as economic information of B. lycium. Because of its high medicinal and market value, it is a warning sign that the plant is highly threatened due to overexploitation. Given this, we suggest to the local and district forestry department, governmental organizations, and non-governmental organizations to encourage, motivate, and also create awareness among the local people to conserve the species for future generations. Keywords: Ethnomedicine; Market value; Traditional knowledge; Berberis lycium; Dir Lower خلاصول شالید: بربیرس لیمیم رایل د درملو بوټو مشهور پیژندل شوی ، د بربریداسای کورنۍ پورې اړه لري ، کوم چې په عام ډول د پاکستان په لویر دیر کې توزیع کیږي. د بی لیمیم برخې لکه ریزومونه او لوبیا د ځایی خلکو لخوا د درملو او خواړو په توګه کارول کیږي. د دې څیړنې کار د بربیرس لیمیم په اړه دوه لوی اړخونه روښانه کوي. لومړی ، د بی لیمیم بیلابیل دودیز او درملو کارول مشخص کول. دوهم ، د خپل منځي ارزښت د لوړې دیر ولسوالۍ په محلي بازارونو کې اسناد ورکول. توکي او میتودونه: نیمه جوړ شوي او خلاص خلاص توکمونه مرکې ، د بازار بازار پوښتنې ، د ساحې مشاهده ، او ډله ییز بحث د می د اکتوبر څخه د اکتوبر تر 2019 پورې ترسره شوي ترڅو د بی لیمکس ایتنو - بوټینیکل موقعیت درک کړي. پایلې: په اوسنۍ څیړنه کې ، د دیر لوئر څخه په مجموعي ډول 61 ځايي خلکو سره مرکه شوې. زموږ د مطالعې د پایلو په اساس ،٪٪. مخبران د ډایبایټس میلیتس درملنې لپاره د بربیرس لیمیم کاروي ، وروسته د هډوکو ترمیم او اسهال تعقیبوي. د اقتصادي ارزښت په نظر کې نیولو سره ، د بی لیمیم ميوه او ریزومونه هم مهم دي. په سیمه ایز ډول ریزوم په یوه کیلو کې له 3 څخه تر 6 امریکایی ډالرو پورې سوداګریزه وه. پایله: دا مطالعه دې پایلې ته رسیدلې چې د لوګر دیر سیمه ایز خلک د درملو ډیر اهمیت لري او د بربیرس لیمیم اقتصادي معلومات. د لوړ درملو او بازار ارزښت له امله ، دا د خبرتیا نښه ده چې کښت د ډیرې اندازې له امله ډیر ګواښل کیږي. دې ته په پام ، موږ د سیمې او ولسوالۍ ځنګلونو ریاست ، دولتي ارګانونو ، او غیر دولتي سازمانونو ته وړاندیز کوو چې د راتلونکي نسل لپاره د کښت ساتنه لپاره د ځایی خلکو په منځ کې پوهاوی ، هڅونه ، او عامه پوهاوی رامینځته کړ. اتنومیتیسین؛ د بازار ارزښت؛ عنعنوي پوهه؛ بربیرس لیمیم؛ ټیټ دی